Carbon Footprint Assessment and Mitigation Options of Dairy under Chinese Conditions - Dong, Hongmin (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
With the rapid human population growth and economic development, demand for animal products continues to increase and livestock production rapidly expands. Greenhouse gases (GHG) emission from livestock research 7.52 billion tons CO2-eq per year, accounting for 50% of agricultural emissions and 18% of global anthropogenic GHG emissions (FAO, 2014), making it become an important source of GHG emissions. The Chinese livestock production emits 373 GHG of million tons CO2-eq. Methane (CH4) emitted from enteric fermentation is 10.74 million tons (equivalent to 225.6 million tons CO2-eq), accounting for 60.7% of total livestock GHG emissions. CH4 emitted from manure management is 3.33 million tons (equivalent to 69.9 million tons CO2-eq), accounting for 18.9% of total livestock GHG emissions. Nitrous oxide (N2O) emitted from manure management is 0.25 million tons (equivalent to 77.2 million tons CO2-eq), accounted for 20.4% of the total livestock GHG emissions (MEE, 2018). The enteric fermentation and manure management contribute 40% to agricultural GHG emissions.